Nitrogen Fertilization of Direct-Seeded Flooded Vs. Transplanted Rice. II. Interactions Among Canopy Properties - Dingkuhn, M.; Schnier, H.F.; De Datta, S.K.; Dorffling, K.; Javellana, C.; Pamplona, R. (Wiley, 1990)
Growth analyses of transplanted and row‐seeded ‘IR64’ rice (Oryza sativa L.) grown in the Philippines at six levels of applied N indicated that growth and CO2 assimilation rates were low during reproductive growth in row‐seeded as compared with transplanted rice. This study sought to quantify the effect on growth of various canopy properties, and to develop a concept for improving yield of direct‐seeded tropical rice. Mathematical relationships among growth parameters were established based on empirical patterns of leaf area index (LAI), foliage N concentration, canopy CO2 exchange rate (CER), and dry matter accumulation. Patterns of tissue death were used to estimate senescence. Relative foliage expansion rates were calculated from LAI patterns. Across all treatments and most developmental stages, uniform response patterns of foliage expansion, tissue death, and CER to LAI and foliage N concentration were observed. With increasing LAI, the minimum foliage N concentration for foliage expansion and tissue maintenance increased. Cessation of foliage expansion and onset of tissue death depended similarly on foliar N status and LAI. Canopy CO2 exchange rate was positively correlated to LAI up to a certian LAI optimum, which depended on foliage N concentration (LAI 3‐6 at 10‐40 g N kg−1). Further increases in LAI reduced CER. Leaf area limited biomass accumulation during the vegetative growth phase, whereas foliage N concentration became limiting thereafter, in all treatments. Overexpansion of foliage was particularly marked in row‐seeded rice, due to the absence of transplanting shock and the high plant density, leading to an unfavorable respiration/photosynthesis ratio. Simulation suggested higher yield for direct‐seeded lowland rice in a modified plant type with lower LAI and higher foliar N concentration during the reproductive growth phase, lower tillering ability, and higher assimilate storage capacity in the stems.